Empirical Analysis on the Factors Affecting Economic Sustainable Development Path in Malaysia: An ARDL Cointegration Approach - Pardi, Faridah; Nawi, Abdol Samad (International Journal of Economics and Financial Issues, 2016)
Through its latest economic model, Malaysia has outlined ‘sustainability’ as the key element to achieve the Vision 2020 – to become a high-income nation by year 2020. This study analyzed the possible factors affecting sustainable development path in Malaysia using the Adjusted Net Savings (ANS) indicator; as projected by World Bank from 1990s. We firstly conducted the ‘Structural break-unit root tests’ to assume stationarity of series with the possible presence of economic shocks during the period of 1972 to 2011. For model estimation, we applied the ARDL technique to find the cointegration between money supply (LFIN), nonrenewable natural resource (fuels, ores and metals) exports (LNR), trade openness (LTRD) and urban population (LURB) with ANS values (LANS). In the short-run, LFIN and LTRD have significant negative impact on LANS while in long run, LNR and LURB tend to have significant negative impact on economic sustainability in Malaysia. Keywords: Adjusted net savings, economic sustainable development path, structural break, Malaysia JEL Classifications: O47; Q01; C32